1999
DOI: 10.1046/j.1440-1584.1999.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Advanced Role of Rural Nurses in New Zealand

Abstract: This paper offers an informative insight into the development of the advanced role of rural nursing practice in New Zealand. Provided is a futuristic vision of nurses' contribution for the provision of primary rural health care. The concept of advanced nursing practice will be discussed within the context of the interdisciplinary healthcare team. It is argued that as nurses take on advanced practice, it is essential they receive appropriate clinical and theoretical skills to ensure they are in a position to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…Most rural hospitals lack on‐site medical staff, and much of the literature focuses on rural nurses taking on advanced and extended practice roles such as radiography, medication prescribing, advanced assessment, and management of trauma and emergencies because of the absence of other health professionals (Robbins 1994, Hegney et al. 1997a, Keyzer 1997, Hegney 1998, Ross 1999, Hegney & McCarthy 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most rural hospitals lack on‐site medical staff, and much of the literature focuses on rural nurses taking on advanced and extended practice roles such as radiography, medication prescribing, advanced assessment, and management of trauma and emergencies because of the absence of other health professionals (Robbins 1994, Hegney et al. 1997a, Keyzer 1997, Hegney 1998, Ross 1999, Hegney & McCarthy 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1999). In rural and remote Australia, like other similar countries where there are few other health professionals (Ross 1999, Rennie et al. 2000, Bushy 2002), it is the nurse who administers and supplies the medication to the client.…”
Section: Discussionmentioning
confidence: 99%
“…1997), Canada (Rennie et al. 2000), New Zealand (Ross 1999) and the US (Bushy 2002). All of these studies found that rural and remote RNs work in an expanded practice role.…”
Section: Introductionmentioning
confidence: 99%
“…Areas where cardiac nurses have shown initiatives include chest-pain clinics, angiography laboratories, cardiac rehabilitation and exercise tolerance testing (Pottle, 2005;Smith, 2002;. Outside cardiovascular nursing, rural primary health initiatives are one example where nurses in New Zealand have advanced in their roles to fill a unique gap (Ross, 1999). Rural isolation and workforce issues have created opportunities for many of the nurse-led initiatives within New Zealand.…”
Section: Advancing Cardiovascular Nursing and Role Expansionmentioning
confidence: 99%